2017
DOI: 10.5539/jas.v9n4p15
|View full text |Cite
|
Sign up to set email alerts
|

Resource Collection by Honeybees (Apis mellifera) on Yellow Melon (Cucumis melo) Flowers

Abstract: This study aimed to analyze the details of collection of floral resources (pollen and nectar) by honeybees (Apis mellifera) on male and hermaphrodite flowers of melon (Cucumis melo). The experiments were conducted in areas located at Embrapa Semiárido and Embrapa Produtos e Mercado, Petrolina, state of Pernambuco, in November and December 2011, with crop of a hybrid yellow 10/00 F1 melon. Honeybee colonies housed in Langstroth hives, uniform concerning the number of individuals and brood area were used. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Perhaps there is a preference of bees for floral resources offered by melon flowers. Previous studies (KIILL et al, 2011;RIBEIRO et al, 2017) have indeed shown that they were the most abundant in visits to melon flowers throughout the observation period.…”
Section: Apis Melliferamentioning
confidence: 72%
See 1 more Smart Citation
“…Perhaps there is a preference of bees for floral resources offered by melon flowers. Previous studies (KIILL et al, 2011;RIBEIRO et al, 2017) have indeed shown that they were the most abundant in visits to melon flowers throughout the observation period.…”
Section: Apis Melliferamentioning
confidence: 72%
“…Because such plants have heavy pollen grains, which are difficult to be carried by the wind, their pollination is entomophilous, that is, insects are the main floral visitors (KIILL et al, 2011). Among visitors to this crop, honey bees (Apis mellifera L.) stand out as effective pollinators, visiting melon flowers throughout the day (SIQUEIRA et al, 2011) in search of nectar and pollen, although at certain times they give preference to one or the other resource (RIBEIRO et al, 2017). In fact, honey bees are essential for the production of fruit in melon (SOUZA et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tschoeke et al (2015) indeed found that bees spent significantly more time collecting pollen than nectar. Ribeiro et al (2017), although using a different methodology, also suggested this.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the nectar, its production by flowers is continuous throughout the day. HF show a higher frequency of visits (Ribeiro et al, , 2017 and are more attractive (Kill et al, 2014), and replenishment of nectar would be lower in areas with the highest number of hives and, therefore, with the highest number of bees visiting the flowers. The nectar would be reduced more rapidly, and this would lead the bees to stay longer on these flowers to collect the resource.…”
Section: Discussionmentioning
confidence: 99%